Spontaneous biliary peritonitis: Is bed side diagnosis possible? - Vijai Datta Upadhyaya; Basant Kumar; Mangal Singh; Rudramani; Sushila Jaiswal; Richa Lal; Sanjay Gambhir; M Rohan (Wolters Kluwer Medknow Publications, 2013)
Background: Spontaneous biliary peritonitis is a rare cause of acute abdomen. In spontaneous biliary peritonitis there is perforation in the wall of the extra-hepatic or intra-hepatic duct occurs without any traumatic or iatrogenic injury and have been described more often in neonates. The symptoms may be acute or insidious delaying the diagnosis. Present manuscript deals with diagnosis and management of these cases. Materials and Methods: This is a prospective study and all patients of suspected biliary peritonitis presented during Dec 2010 to Feb 2012 were included in the study. After preliminary investigations in all patients abdominal paracentesis was done and in cases where intra-abdominal fluid bilirubin level was several fold higher than serum bilirubin level were subjected to exploratory laparotomy. Further investigation like T-tube cholangiogram and magnetic resonance cholangiopancreatography (MRCP) was done to rule out choledochal cyst before leveling these cases as SPBD. Results: A total of 6 patients were included in present series commonest presenting symptom was progressive abdominal distension without signs of overt peritonitis followed by progressive jaundice, fever and abdominal pain. On exploration site of perforation was observed in 50% of cases and in 50% of cases bile duct was not dilated. Second surgery was not required in 34% of cases. There was no mortality or significant morbidity in our series. Conclusion: Spontaneous perforation of bile duct is rare disease and high index of suspicion is required for diagnosis. Simple bed side test can help in diagnosis but T tube cholangiogram or MRCP are must to rule out choledochal cyst.